Photosynthesis and whole-plant carbon balances of warm affinity Halophila nipponica and cold affinity Zostera marina in relation to water temperature rise: implication for future geographic distribution - Kim, Seung Hyeon; Kim, Hyegwang; Suonan, Zhaxi; Zhang, Fei; Lee, Kun-Seop (Frontiers in Marine Science, 2023)
Climate change associated sea surface temperature rise could significantly affect the physiology, and consequently geographic distribution of seagrasses. Photosynthetic and respiratory responses of warm affinity Halophila nipponica and cold affinity Zostera marina to a change in water temperature (7–26°C) were investigated to estimate whole-plant carbon balance for prediction of the future geographic distributions of these seagrasses in the northwestern Pacific region. It was hypothesized that H. nipponica and Z. marina showed distinctly different patterns of carbon balance with changes in water temperature. Photosynthetic and respiratory rates of H. nipponica and Z. marina generally increased with increasing water temperature, except for Ic and Ik of H. nipponica and α of Z. marina. H. nipponica showed high Pmax and α values, which could support a greater respiratory demand related to the higher proportion of non-photosynthetic tissues (~67%), compared with Z. marina (~34%). The whole-plant carbon balance of Z. marina remained positive throughout the experiment, although it decreased to nearly zero during the high water-temperature period. H. nipponica exhibited a negative carbon balance during winter and early spring, which corresponded with severely limited growth at water temperatures< 15°C. These results suggest that increases in water temperature, particularly during winter, in relation to continuous climate change, could induce substantial changes in the seagrass ecosystem structure and corresponding changes in coastal ecosystem services in the temperate coastal waters of the northwestern Pacific region. The results of this study will provide valuable information on the effective management and conservation of coastal and estuarine ecosystems under ongoing climate change.